2019
DOI: 10.1029/2018jf004762
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Versus Tectonics: The Case of 2016 Amatrice and Norcia (Central Italy) Earthquakes Surface Coseismic Fractures

Abstract: The 2016 central Apennines earthquake sequence was caused by slip on an extensional fault system and resulted in sizable coseismic surface deformation. The most evident effects occurred along the western slope of Mount Vettore, a geologically and morphologically complex mountain ridge. Steep topography and rheological contrasts are known to have strongly controlled the coseismic deformation pattern during a number of different earthquakes that occurred in mountainous areas worldwide. Nevertheless, so far the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…This landsliding could have been reactivated by shaking induced by the stronger and closer M w 6.5 30 October 2016 earthquake, thereby adding some gravity-driven motion to the predominant tectonic slip component. The recent geomechanical model of Di Naccio et al (2019) also heads in this direction, showing that the steep western slope of Monte Vettore is prone to destabilization, in particular due to the presence of tectonic faults marking the contact between lithologies with contrasting mechanical behavior.…”
Section: 1029/2019tc005596mentioning
confidence: 87%
“…This landsliding could have been reactivated by shaking induced by the stronger and closer M w 6.5 30 October 2016 earthquake, thereby adding some gravity-driven motion to the predominant tectonic slip component. The recent geomechanical model of Di Naccio et al (2019) also heads in this direction, showing that the steep western slope of Monte Vettore is prone to destabilization, in particular due to the presence of tectonic faults marking the contact between lithologies with contrasting mechanical behavior.…”
Section: 1029/2019tc005596mentioning
confidence: 87%
“…In the specific case of central Apennines, Kastelic et al (2017) and Stemberk et al (2019) have shown that fault scarps that separate footwall carbonate bedrock from hanging wall carbonate talus, possibly representing the surface extension of upper crustal seismogenic faults, are exhumed also by nontectonic processes, making it hard to detect and quantify the long-term tectonic deformation. Moreover, even surface coseismic ruptures reflect the influence of gravity and rheology, as shown for the 24 August 2016, Amatrice earthquake, and for the 30 October 2016, M w 6.5 Norcia earthquake (Di Naccio et al, 2019;Huang et al, 2017). It follows that discarding as marginal these surficial processes, that is to say, not removing their characteristic signature from the total deformation, may lead to a gross overestimation of the slip per event, and ultimately of the long-term slip rate.…”
Section: Introductionmentioning
confidence: 98%
“…There is a wealth of scientific literature demonstrating the benefits of InSAR to monitor a wide spectrum of urban processes, such as subsidence [2][3][4][5], foundation settlement [1,6,7], deformation of new buildings [8], surface effects due to tunneling [9][10][11], ground motions associated to faults and local tectonics [12][13][14]. The implementation on real case studies proves the increasing use of these techniques on a routine basis and how they can influence the management of infrastructure assets and preservation of the built environment [1,15,16].…”
Section: Introductionmentioning
confidence: 99%